2017
DOI: 10.4103/ijccm.ijccm_140_17
|View full text |Cite
|
Sign up to set email alerts
|

Colistin nephrotoxicity in adults: Single centre large series from India

Abstract: Context:Limited Indian data are available on the rate of colistin nephrotoxicity and other risk factors contributing to the development of this important side effect.Aim:This study aims to generate data on colistin nephrotoxicity from a large cohort of Indian patients.Design:Retrospective cohort study.Materials and Methods:Case record analysis of patients who received colistin, in an oncology center in India, between January 2011 and December 2015. Nephrotoxicity was assessed using risk, injury, failure, loss,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This could be due to less impurities present in the newer colistin preparations and better understanding of fluid management strategies in septic patients in modern intensive care units. 4,1012 The nephrotoxicity rate in a recently published study from our own center was 13.3%. 12 Concomitant use of vancomycin, abnormal baseline creatinine, ICU stay, and higher disease severity were associated with higher rates of nephrotoxicity in patients on colistin.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This could be due to less impurities present in the newer colistin preparations and better understanding of fluid management strategies in septic patients in modern intensive care units. 4,1012 The nephrotoxicity rate in a recently published study from our own center was 13.3%. 12 Concomitant use of vancomycin, abnormal baseline creatinine, ICU stay, and higher disease severity were associated with higher rates of nephrotoxicity in patients on colistin.…”
Section: Discussionmentioning
confidence: 93%
“…4,1012 The nephrotoxicity rate in a recently published study from our own center was 13.3%. 12 Concomitant use of vancomycin, abnormal baseline creatinine, ICU stay, and higher disease severity were associated with higher rates of nephrotoxicity in patients on colistin. 12…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Therapeutic doses varied greatly across the studies: for example, where intravenous colistin maintenance dosages for patients with normal renal function were reported in million Internation Units (MIU) per day, the daily dose ranged from 1 to 36 MIU. Sixteen studies in the secondary analysis population reported nephrotoxicity rates in subgroups of patients by polymyxin dose [10,17,30,52,92,106,108,113,130,151,181,198,206,215,221,232]; cutoffs varied between studies but were used to create high, intermediate and low dose subgroups that, in general, corresponded to intravenous colistin doses of more than 9 MIU per day, 6e9 MIU per day and less than 6 MIU per day, respectively (Supplementary Table S3). There was a significant difference in the rate of nephrotoxicity between subgroups of patients receiving high, intermediate and low polymyxin doses (0.446 (95% CI 0.367e0.528), 0.374 (95% CI 0.280e0.478) and 0.284 (95% CI 0.224e0.352), respectively; p 0.001; Fig.…”
Section: Nephrotoxicitymentioning
confidence: 99%